Design My Music Instrument: A Project-Based Science, Technology, Engineering, Arts, and Mathematics Program on The Development of Creativity - Cheng, Li; Wang, Meiling; Chen, Yanru; Niu, Weihua; Hong, Mengfei; Zhu, Yuhong (Frontiers in Psychology, 2022)
Creativity is an essential factor in ensuring the sustainable development of a society. Improving students' creativity has gained much attention in education, especially in Science, Technology, Engineering, Arts, and Mathematics (STEAM) education. In a quasi-experimental design, this study examines the effectiveness of a project-based STEAM program on the development of creativity in Chinese elementary school science education. We selected two fourth-graders classes. One received a project-based STEAM program (the experimental group, n=33), and the other received a conventional science teaching (the control group, n=33) over six weeks. Students' creativity was assessed before and after the intervention using a multi-method approach, including a test of divergent thinking, a story completion through the Consensus Assessment Technique (CAT), a creative self-efficacy measure, and a group-based creative project. Moreover, all students received a test of their science knowledge after the intervention. The results showed that compared with the control group, the creativity of the experimental group students improved significantly for six weeks at both individual and group level, even though their knowledge in science were comparable. This result confirmed the effectiveness of a project-based STEAM educational program improving elementary school students' creativity. Implications are discussed.